Hosting capacity of distributed generation based on holomorphic embedding method in distribution networks - Xie, Jiarui; Tang, Fei; Qi, Junfeng; Li, Xinang; Lin, Zhiyuan; Liu, Zhuo; Guo, Yuhan (Frontiers in Energy Research, 2023)
Considering the voltage rise problem caused by integrating large-scale distributed generation into the distribution networks, a distributed generation hosting capacity assessment method based on the improved holomorphic embedding method is proposed. First, the relationship between distributed generator penetration and voltage at the access point is explored and voltage violation is used as a constraint to solve the hosting capacity. Secondly, a self-defined directional holomorphic embedding method is proposed based on the classical model, further, the safety region under voltage constraints is derived. The intersection of the bus trajectory with the boundary of the voltage constraint region is used as the criterion for judging the maximum hosting capacity of distributed generation under a single access scenario. Then, a sufficient number of distributed generation access scenarios are generated using Monte Carlo, and the proposed criterion is used to solve the hosting capacity under each scenario. The cumulative distribution curve is obtained by statistically solving admission capacity data, which can represent the relationship between the level of voltage violation risk and the hosting capacity of distributed generation. The validity and correctness of the proposed method are verified on the IEEE 22-bus distribution network.